2021
DOI: 10.1245/s10434-021-10487-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Disparities in Postmastectomy Breast Reconstruction and Strategies for Mitigation

Abstract: For many women, breast reconstruction is an essential component of the breast cancer care continuum after mastectomy. Despite postmastectomy breast reconstruction now being a standard of care, numerous studies over the past decade have documented persistent racial disparities in breast reconstruction rates, physician referral patterns, and patient knowledge of their reconstructive options. These disparities have disproportionately impacted women of color-most specifically, African American women. Recent data h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…21,22 Previous studies examining the distribution of resources across demographics showed significant disparities among racial and socioeconomic groups with varying affordability and availability of reconstructive services. 21,23 Further, access to postmastectomy reconstruction has been shown to be influenced by referral patterns of oncologists and general surgeons. 9,23,24 To address these barriers, the 1998 WHCRA was introduced at the national level to mandate insurance coverage of postmastectomy breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Previous studies examining the distribution of resources across demographics showed significant disparities among racial and socioeconomic groups with varying affordability and availability of reconstructive services. 21,23 Further, access to postmastectomy reconstruction has been shown to be influenced by referral patterns of oncologists and general surgeons. 9,23,24 To address these barriers, the 1998 WHCRA was introduced at the national level to mandate insurance coverage of postmastectomy breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Postmastectomy reconstruction has now been integrated into the standard of care for breast cancer because of its documented benefits for patient health-related quality of life, body image, and psychosexual well-being 21,22 . Previous studies examining the distribution of resources across demographics showed significant disparities among racial and socioeconomic groups with varying affordability and availability of reconstructive services 21,23 . Further, access to postmastectomy reconstruction has been shown to be influenced by referral patterns of oncologists and general surgeons 9,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Although this retrospective study cannot determine causation between minority patient caseloads and MIPS scores, there has been extensive prior work investigating disparities in plastic surgery access and outcomes. 14,[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] There is increased recognition of the role of zip codes in predicting health outcomes, based on historical segregation, community resources, and policy. 21 For example, breast cancer reconstruction rates are higher in areas with a higher density of plastic surgeons, but the rate is lower for nonwhite patients.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] A diverse community of plastic surgeons that reflects the complexity of the United States population is paramount to reducing inequities in access to reconstructive surgeries. 21,22 Additionally, physicians from historically marginalized ethnic backgrounds are more likely to serve minority and underserved communities at a greater frequency than majority physicians. 23 There is recent evidence that patient reported outcomes and compliance can be influenced by the background of the plastic surgeons who treats them.…”
Section: Strength In Diversitymentioning
confidence: 99%